tert-Butyl 4-(4-chloroanilino)-6-methyl-2-oxocyclohex-3-enecarboxylate - Ray J. Butcher; Kenneth R. Scott; Henry North; Mariano S. Alexander (Acta Crystallographica Section E, 2011)
In the title compound, C18H22ClNO3, the dihedral angle between the benzene ring and the conjugated part of the enaminone ring is 55.19 (9)°. The ester substituent makes a dihedral angle of 81.0 (2)° with this latter moiety. The crystal structure features N—H...O and weak C—H...O intermolecular interactions.